2017
DOI: 10.1590/2177-6709.22.2.045-054.oar
|View full text |Cite
|
Sign up to set email alerts
|

Discoloration and force degradation of orthodontic elastomeric ligatures

Abstract: OBJECTIVE: The aim of the present study was to evaluate color changes and force degradation of orthodontic elastomeric ligatures in different stretching patterns during a 8-weeks period. METHODS: Two elastomers with the minimum and two with the maximum color changing, and gray elastomers of two brands (American Orthodontics and Ortho Technology) were selected according to an opinion poll with clinicians and color changes after 4 weeks of intraoral use were evaluated. These elastomers were mounted on special ji… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 24 publications
3
18
0
2
Order By: Relevance
“…[4,9] The results of research conducted are consistent with research conducted by Mirhashemi et al where the decrease in strength after the first 24 h occurred at 20.7%-31.2% in elastomeric chains of thermoplastic materials and 9.3%-12.4% in elastomeric chains of thermoset materials. [5,8] The greatest decrease in strength that occurs after the first 24 h is also in accordance with the research conducted by Yagura et al, [10] where the greater the initial strength given to elastomeric chains, the greater the decrease in strength that occurs. Buchmann et al [3] and Mirhashemi et al [8] suggested that the decrease in strength up to the seventh day was caused by absorption of saliva and formation, which coincided with hydrogen adhesion between water molecules and elastomeric macromolecules.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…[4,9] The results of research conducted are consistent with research conducted by Mirhashemi et al where the decrease in strength after the first 24 h occurred at 20.7%-31.2% in elastomeric chains of thermoplastic materials and 9.3%-12.4% in elastomeric chains of thermoset materials. [5,8] The greatest decrease in strength that occurs after the first 24 h is also in accordance with the research conducted by Yagura et al, [10] where the greater the initial strength given to elastomeric chains, the greater the decrease in strength that occurs. Buchmann et al [3] and Mirhashemi et al [8] suggested that the decrease in strength up to the seventh day was caused by absorption of saliva and formation, which coincided with hydrogen adhesion between water molecules and elastomeric macromolecules.…”
Section: Discussionsupporting
confidence: 87%
“…Deformation mechanisms are related to chain slippage and molecular stretching. [5] Thermoplastic and thermoset chains are different manufacturer's materials of elastomeric chains. Thermoplastic is a plastic that is softened by heating and will harden when cooled.…”
Section: Introductionmentioning
confidence: 99%
“…2,[17][18][19] Orthodontics, a dental specialty that works directly with smile aesthetics, requires continuous updating of its material collection to keep up with the demands of the overall population. 4,5,[20][21][22][23][24] Therefore, testing the color change of elastomeric ligatures is required to guide orthodontists seeking to respect the decision of patients desiring an aesthetic smile even during orthodontic treatment. Therefore, several studies have been conducted 1, [6][7][8][9][10][11][12][13]15,16 with the aim of explaining which of the aesthetic elastomeric ligatures have the least effect on smile aesthetics.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 17 - 19 Orthodontics, a dental specialty that works directly with smile aesthetics, requires continuous updating of its material collection to keep up with the demands of the overall population. 4 , 5 , 20 - 24 …”
Section: Discussionmentioning
confidence: 99%
“…Elastomer chains can be classified as short, medium or long according to the distance between the links 5,6 . They have the advantages of being practical, hygienic, having elastic memory, being easy to place and comfortable for the patient to use, biocompatible and inexpensive [7][8][9] . However, they also have disadvantages because they are incapable of releasing constant levels of force for a long period of time and undergo changes in their physical properties when exposed to the oral environment, where they absorb saliva and become deformed due to breakdown of internal bonds.…”
Section: Introductionmentioning
confidence: 99%